Kemudahterancaman (vulnerability) penduduk terhadap perubahan guna tanah di Selangor - Shaharudin Idrus,; Lim, Choun Sian; Abdul Samad Hadi, (Environmental Management Society, Malaysia, 2004)
The changes in land use and land cover indicate the development changes that occur at a certain place. Selangor has an area of 796,084 hectares and consists of nine districts. The state government of Selangor plans to achieve the most developed state status by the year 2005. Consequently, land use patterns have changed tremendously, especially within the past five years. The change in land use, especially from forest to non-forest, results in environmental degradation that will eventually threaten human life in that particular area. Whether we realize it or not, the change in land use may increase people’s vulnerability in a society that tries to achieve development in line with the framework of sustainable development. This article will examine the changes in land use and land cover which has occurred within the last four decades (1966-2001) using Geographical Information Systems (GIS) and its relationship with vulnerability to human life in the surrounding area. In this context, the driving forces to the changes will be looked at in a holistic and integrated manner. Among the driving forces of change that will be discussed are state development policies, foreign direct investment, population change, urbanization and infrastructure development